Answer:
B: -6+2i
Step-by-step explanation:
- 3i + (-6 - i) = ⇒ open parenthesis
- 3i - 6 - i = ⇒ simplify
- -6 + 2i ⇒ answer in standard form of a+bi
Answer:
see explanation
Step-by-step explanation:
To prove that BC ≅ AD, that is that BC = AD
You would need to prove the lengths are the same.
Answer:
![5\frac{1}{9}](https://tex.z-dn.net/?f=5%5Cfrac%7B1%7D%7B9%7D)
Step-by-step explanation:
When dividing 46 by 9 quotient is 5 and remainder is 46 - 45 = 1
![5\frac{1}{9}](https://tex.z-dn.net/?f=5%5Cfrac%7B1%7D%7B9%7D)
Answer:
Step-by-step explanation:
Slope of perpendicular lines = -1
y = 5/2x + 3
![m_{1}=\frac{5}{2}\\\\m_{1}*m_{2}=-1\\\\](https://tex.z-dn.net/?f=m_%7B1%7D%3D%5Cfrac%7B5%7D%7B2%7D%5C%5C%5C%5Cm_%7B1%7D%2Am_%7B2%7D%3D-1%5C%5C%5C%5C)
-1 ÷ ![m_{1}](https://tex.z-dn.net/?f=m_%7B1%7D)
= ![-1*\frac{2}{5}=\frac{-2}{5}](https://tex.z-dn.net/?f=-1%2A%5Cfrac%7B2%7D%7B5%7D%3D%5Cfrac%7B-2%7D%7B5%7D)
(-3 , -5)
Equation of the required line: y - y₁ = m(x -x₁)
y - [5] = ![\frac{-2}{5}(x - [-3])\\](https://tex.z-dn.net/?f=%5Cfrac%7B-2%7D%7B5%7D%28x%20-%20%5B-3%5D%29%5C%5C)
![y+5=\frac{-2}{5}x + 3*\frac{-2}{5}\\\\y+5=\frac{-2}{5}x-\frac{6}{5}\\\\ y =\frac{-2}{5}x-\frac{6}{5}-5\\\\ y = \frac{-2}{5}x-\frac{6}{5}-\frac{5*5}{1*5}\\\\ y = \frac{-2}{5}x-\frac{6}{5}-\frac{25}{5}\\\\\\ y=\frac{-2}{5}x-\frac{31}{5}](https://tex.z-dn.net/?f=y%2B5%3D%5Cfrac%7B-2%7D%7B5%7Dx%20%2B%203%2A%5Cfrac%7B-2%7D%7B5%7D%5C%5C%5C%5Cy%2B5%3D%5Cfrac%7B-2%7D%7B5%7Dx-%5Cfrac%7B6%7D%7B5%7D%5C%5C%5C%5C%20%20%20y%20%3D%5Cfrac%7B-2%7D%7B5%7Dx-%5Cfrac%7B6%7D%7B5%7D-5%5C%5C%5C%5C%20%20%20y%20%3D%20%5Cfrac%7B-2%7D%7B5%7Dx-%5Cfrac%7B6%7D%7B5%7D-%5Cfrac%7B5%2A5%7D%7B1%2A5%7D%5C%5C%5C%5C%20y%20%3D%20%5Cfrac%7B-2%7D%7B5%7Dx-%5Cfrac%7B6%7D%7B5%7D-%5Cfrac%7B25%7D%7B5%7D%5C%5C%5C%5C%5C%5C%20y%3D%5Cfrac%7B-2%7D%7B5%7Dx-%5Cfrac%7B31%7D%7B5%7D)
Answer:
114,688
Step-by-step explanation:
the previous term is multiplied by 4 to get the next term.if you continue with this sequence you would eventually get 114 688